CHAOPHRAYA River Resources Management Affecting the Success of Flood Prevention in Bangkok Metropolitan - ขันตี, อดิศักดิ์; เลาหวิเชียร, อุทัย (Business Administration and Management Journal Review, 2016)
This research aims at analyzing different approaches to the Chaophraya River water resource management which affect the success of flood prevention in the Bangkok metropolitan area. These approaches are government’s policy, public participation, water resource management networking, and coordination among relevant agencies within the Bangkok Metropolitan Administration (BMA). The samples of this study were the leader of Department of drainage and sewerage ,The leader of District office , the government employee and the leader of community in bangkok. The data were collected using in-depth interview. The result of the study on each approach is summarized as follows. 1. Governments’ policy: Interprovincial cooperation among different agencies concerned cannot be successfully achieved unless the government has developed a clear and definite policy relating to the issue. 2. Public participation: Public participation is not exercised on a continuous basis. What is lacking are brainstorming process as well as joint action and follow-up. People play their part in flood prevention only during campaigns on special occasions and when the district office’s operation is needed. 3. Water resource management networking: Cooperation networks for flood prevention and mitigation are formed when flooding occurs and on special occasions in response to district office’s request and campaigns. These networks, however, dissolve at the end of the flood. 4. Inter-agency coordination within the BMA: The Flood Control Center under the Department of Drainage and Sewerage (DDS) and the joint operations center of each of the 50 district offices coordinate with other relevant agencies in preventing and fighting flood in all parts of Bangkok. The success of flood control coordination relies mainly on the leadership and congeniality of the executives of the DDS and district offices.